2001
DOI: 10.1088/0963-0252/10/2/323
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal glow discharges in Ar: experiments and models

Abstract: We review measured and calculated voltages and cathode-fall thicknesses against current and electrode separation for parallel-plane Ar glow discharges in the above-normal, or abnormal, current range. We consider dc and pulsed discharges, but not radio-frequency discharges. Reasons for the very high degree of variability among experiments and models are reviewed and suggestions are made for improving the reliability of both. Variations of a factor of two in experimental cathode-fall voltages at a fixed normaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 116 publications
(351 reference statements)
3
64
1
1
Order By: Relevance
“…At a high pressure, i.e., 10 Torr, on the other hand, the I-V characteristics show positive resistance. We note that, at lower pressures, the I-V characteristics is also different from the well-known I-V characteristics Jn -2 (here, J is the current density and n is the neutral particle density) scaling in the absence of a magnetic field [11].…”
Section: Current-voltage Characteristicscontrasting
confidence: 73%
See 1 more Smart Citation
“…At a high pressure, i.e., 10 Torr, on the other hand, the I-V characteristics show positive resistance. We note that, at lower pressures, the I-V characteristics is also different from the well-known I-V characteristics Jn -2 (here, J is the current density and n is the neutral particle density) scaling in the absence of a magnetic field [11].…”
Section: Current-voltage Characteristicscontrasting
confidence: 73%
“…3. The breakdown voltage curves with a magnetic field show more interesting features at lower pressures (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Torr in the case of He discharges). When the electrode with the magnetic circuit is powered at negative voltages, the breakdown voltages are found to be significantly lower than those for discharges without magnetic field.…”
Section: Breakdown Voltage Measurementsmentioning
confidence: 99%
“…by the long path breakdown [15]. The second scaling that has been tested is j/p 2 , which is connected to the effect of space charge [17]. It was shown that for standard size discharges both pd (and E/N) and j/p 2 scalings are valid in parameter region around Paschen minimum [11].…”
Section: Properties Of Micrometer Size Discharges -Scaling Lawsmentioning
confidence: 99%
“…Our knowledge on basic processes in standard size discharges provided us with a possibility to investigate basic properties of micro-discharges from the point of view of scaling laws [16,17]. This type of nonequilibrium discharges with rising number of applications is inaccessible for most standard diagnostic tools due to its small size.…”
Section: Introductionmentioning
confidence: 99%
“…This is in principle identical to electron-hybrid models used in lowpressure glow discharges. 13 Its development is built on our previous work 12 and is similar to that used recently for radiofrequency APGD. 11 It is worth mentioning that the hybrid approach has achieved quantitative agreement with most available experimental data for DC APGD ͑Ref.…”
Section: Introductionmentioning
confidence: 99%